Mengungkap Makna Pendapatan dalam Perspektif Sopir Bus di Masa Pandemi Covid-19 - Ihda Izzatul Alfaini; Mochammad Ilyas Junjunan; Ajeng Tita Nawangsari (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2023)
Purpose: This study aims to understand in depth the meaning of income according to the perspective of city transportation bus drivers at the Paciran terminal during the COVID-19 pandemic. In this study, the meaning of income is formed by the environment of the city transport bus drivers.Method: This study uses the approach with the interpretive paradigm of Husserl's transcendental phenomenology. The phenomenological method emphasizes the meaning that arises from each individual's experience and awareness. Results: The results showed that the informants had different meanings of income. Income is interpreted as a form of material used to meet family needs and future savings. Income is a non-material form, namely the income of inner satisfaction by feeling happy because it helps passengers who need transportation, and income is a spiritual form by applying "flexible" fares to passengers who need transportation for humanitarian purposes, It is believed that someone will get more sustenance than what is given to others because sustenance has already been arranged.Implications: This study reveals the meaning of income from the perspective of bus drivers. The approach through different professions but close to the community provides expansion and development of accounting theory from various existing perspectives, including the internalization of local wisdom values in it.Novelty: This study has a novelty in Hurssel's phenomenological approach in the context of the meaning of income from the perspective of bus drivers which has a meaning that is contrary to the concept of accounting theory.